PEMBIAYAAN MURABAHAH DALAM PERSPEKTIF FIQH ISLAM, HUKUM POSITIF DAN HUKUM SYARIAH - tri setiady (Fiat Justisia: Jurnal Ilmu Hukum, 2014)
Murabaha financing. Murabaha is an agreement of sale and purchase between the two parties, in which the buyer and seller agree on the sale price; which consists of purchase price plus purchase costs and profits for sellers. Another understanding of Murabaha is an agreement of sale and purchase by declaring the acquisition cost and the benefits agreed upon by the seller and buyer. Murabaha can be made in cash, or also pay in installments. Another understanding of Murabaha is a sale and purchase transactions, which is the bank received a number of advantages. In this case, the bank become a seller and customers into buyers. Keywords: Murabaha Financing, Positive Law and Sharia Law